Water-Soluble Inorganic Anions in Fine Particulate Matter (PM2.5) in Dhaka, Bangladesh: Source Apportionment - Riadul Rumman; Md Rezaul Haq; Md Masudur Rahman Rahat; Farhana Jahan; Shyama Prosad Moulick; Refayat Nigar; Chandan Halder; Wenbin Liu; Farhana Khanam Ferdousi; Ahsan Habib (Journal of Chemistry)
Bangladesh is one of the most populated countries in the world. More than 200 air quality index values were recorded in January and February since 2017, indicating that the air quality was unhealthy to very unhealthy. In this work, water-soluble inorganic anions (WSIAs) in fine particulate matter (PM2.5) in Dhaka, the capital of Bangladesh with a population of around 21 million, were evaluated. Accordingly, PM2.5 was collected using a quartz filter coupled with an active air sampler set in Dhaka University campus, Bangladesh, during February 2023, to analyze WSIAs. The 24-h average PM2.5 mass, 156 ± 44.8 μg/m3, was almost nine times higher than the WHO limit values of 15.0 μg/m3 and about three times higher than the Bangladesh Department of Environment limits of 65.0 μg/m3. Fluoride, chloride, bromide, nitrite, nitrate, phosphate, and sulfate were among the water-soluble ions that were determined using ion chromatography. While bromide and nitrite were found to be below the detection limit, the mean concentrations of fluoride, chloride, nitrate, phosphate, and sulfate were determined to be 0.086 ± 0.010, 2.27 ± 0.332, 10.2 ± 1.29, 2.23 ± 0.424, and 11.0 ± 1.45 μg/m3, respectively. The highest levels of PM2.5 and the relevant anions were determined to be present during February 9-10, 2023. Sulfate accounted for almost 43% of the anions in the overall PM2.5. According to the results of the statistical analysis, the high concentrations of sulfate and nitrate in PM2.5 in Dhaka, Bangladesh, were primarily caused by sulfur-containing fossil fuels, especially sulfur-containing diesel, coal, and unfit automobiles, while the main sources of fluoride and chloride were fire retardants, burning of textile, and municipal solid wastes. All of these sources have the ability to produce PM2.5.